Decentralization, Forests and Rural Communities : Policy Outcomes in South and Southeast Asia - EDWARD L. WEBB , GANESH P. SHIVAKOTI (Sage Publications India, 2007)
‘Centralize!’ ‘Decentralize!’ ‘No, centralize. We need more control!’, ‘We must decentralize! Centralizing is not working.’ Organizations and agencies around the world have gone through reversing this pendulum swing time and again, in an effort to improve management or to make their programs more effective and efficient. But they find it difficult to truly know which aspects to control at which level. So when they arrive at one or the other pole, problems and unintended consequences become evident and they swing back. The same is true for the way governments and agencies handle forest and tree resources. Many countries in the past, and even today, have nationalized ownership and management of forestland or even of specific tree species. They often do this with the expectation that they will have more control, increased revenue and in some cases longer term sustainability. But there is a multitude of examples of centralizing not reaching these goals and the resource finally becoming so degraded that it is no longer of much interest to the central authority.